Advance voting with same-day registration: the impact on turnout in New Zealand. (4th May 2018) - Garnett, Holly Ann
ABSTRACT: In-person advance voting has risen dramatically in New Zealand during recent elections: from only 11% of voters in 2008 to nearly half of voters in the 2017 general election. With such a popular programme, scholars and practitioners must question the implications of advance voting. This article considers two questions. First, did advance voting, implemented alongside same-day registration opportunities, increase turnout in 2017? Second, what are the characteristics of the areas with the highest rates of, and increases in, advance voting? This article employs the data published by the Electoral Commission and Census to provide precise assessments of the impact of advance voting in New Zealand. It finds that advance voting, when combined with on-site registration on advance voting days, increases turnout by about 7.6 percentage points in 2017. Furthermore, high rates of, and increases in, advance voting are predominant in areas with low levels of home ownership, which this article theorises is related more to urban environments, than income levels. Advance voting is also negatively related to levels of turnout, suggesting that this electoral reform is not only increasing in areas with existing high turnout cultures.